A 4-year profile of game demands in elite women's division I college basketball - Ransdell, L. B.; Murray, T.; Gao, Y.; Jones, P.; Bycura, D. (The Journal of Strength and Conditioning Research, 2020)
Workload for a Division I women's collegiate basketball team (0.817 win percentage) was examined by: (a) season, (b) player position, and (c) game outcome (wins vs. losses). Female athletes (n = 6, mean 19.7 ± 1.5 years, at beginning of study) wore Catapult S5 units during 91.8% of games over a 4-year period. Average PlayerLoad, PlayerLoad per minute (PL·min-1), high inertial movement analysis (high-IMA), and jumps were quantified using Catapult Openfield software (version 1.14.1+). Data were checked for normality and log- or square-root-transformed when they were non-normal. A series of linear mixed model analyses were conducted to detect differences in PlayerLoad, PL·min-1, high-IMA, and jumps by season, position, and game outcome. PL·min-1 and jumps data were not normal, so they were transformed, analyses were run; because there were no differences in findings, data are reported in original units to allow for comparisons with other studies. Cohen's d and confidence intervals were provided as additional information about the strength of reported differences. The 3 most consistent findings were that across a 4-year period, jumps increased, PL·min-1 was higher in guards compared with posts, and high-IMA was higher in losses compared with wins. Other workload patterns were inconsistent, and inappropriate for making conclusive statements. Therefore, comparing jumps across multiple seasons, PL·min-1 by player position and high-IMA in losses are important; in addition, all data can be used to profile National Collegiate Athletic Association Division I women's basketball players and set game workload expectations.